Analisis Prediksi Kebangkrutan dan Pengaruhnya terhadap Nilai Perusahaan PT. Unilever Indonesia Tahun 2022 (Metode Altman Z-Score Modifikasi) - Ayu Puspitaningtyas; Muhammad Shiddiq (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to analyze and determine the company's financial performance, potential bankruptcy with the Altman Z-Score Modification approach and analyze the effect of bankruptcy predictions on the value of firm in PT. Unilever Indonesia Tbk in 2022. The method used in the study with the Altman Z-Score Modified method. This Altman model is very useful for companies to find out the condition of the company during the current period as well as simple linear regression with IBM SPSS Statistic 26 software. The data in this study was obtained by processing data on the quarterly financial statements of PT. Unilever Indonesia Tbk for the period of Q1 2015 to Q2 2022. The results showed in regression research, altman Z-Score's potential bankruptcy had a significant negative effect on the value of the firm.